A novel rapid bioluminescence-based antimicrobial susceptibility testing method based on adenosine triphosphate consumption - Sever, Elif Arik; Aybakan, Esma; Beşli, Yeşim; Karatuna, Onur; Kocagoz, Tanil (Frontiers in Microbiology, 2024)
Introduction: Standard, phenotypic antimicrobial susceptibility testing (AST) methods require 16-20 h of incubation and are considered as the bottleneck in providing timely input for appropriate antimicrobial treatment. In this study, a novel adenosine triphosphate (ATP)-bioluminescence-based method which allows rapid AST within three hours was described. Methods: Standard AST was performed for 56 Enterobacterales isolates using EUCAST disk diffusion (DD) methodology. For the bioluminescence-based rapid AST, suspensions of bacteria were prepared using Mueller-Hinton broth to obtain a turbidity of 0.5 McFarland. The suspensions were distributed into 96-well microtiter plates. ATP (20 mM) and fixed concentrations of different antibiotics were added. Following incubation at 37°C for one hour, a luminescent reaction mixture, including the substrate luciferin and luciferase enzyme solutions, was added. The chemiluminescence was monitored using an imaging system. Light production demonstrated the presence of ATP, indicating that the isolate was susceptible to the antibiotic in the well. Absence or decrease of light intensity, compared with the growth control well, indicated the use of ATP as an indirect measure of bacterial growth, and therefore resistance to the antibiotic in the well. Results: The novel AST method was tested using a total of 348 test wells. Concordance was achieved for 290 (83.3%) of the tests, whereas 52 (14.9%) and 6 (1.7%) tests caused minor and major errors, respectively. Discussion: In this study, a bioluminescence-based rapid AST was developed based on the consumption of ATP by bacteria. Our method's uniqueness relies on determining ATP consumption by microorganisms in the presence or absence of an antibiotic. The novel AST method described in this study lays the groundwork for obtaining rapid results, which should be considered as a proof of concept. With further optimization studies, this novel method can provide higher accuracy and be introduced into clinical practice as a routine AST method.